Model Pengembangan Bank Sampah Berbasis Masyarakat untuk Mendukung Pengelolaan Lingkungan Hidup dan Pembangunan Ekonomi Lokal di Kawasan Gunung Lawu - Sutirto, Tundjung Wahadi; Marwanti, Sri; Sugiarti, Rara (ENVIRO: Journal of Tropical Environmental Research, 2022)
The long-term objective of the research on "Community-Based Waste Bank Development Model to Support Environmental Management and Local Economic Development in the Mount Lawu Area" is to develop waste banks to support environmental management and improve the local economy in the Mount Lawu area. In particular, this study aims to: (1) identify waste bank development activities that have been carried out by communities in the Mount Lawu area, (2) find out the role of local institutions in developing community-based waste banks to support environmental management, (3) know internal and external obstacles in the development of community-based waste banks to support environmental management and improve the local economy in the Mount Lawu area, (4) identifyi supporting factors for the development of community-based waste banks to support environmental management and improving the local economy in the Mount Lawu area, (5) knowing the benefits of community-based waste bank development for the environment and strengthening the local economy in the Mount Lawu area, (6) find out the Karanganyar District Government policies and programs in developing community-based waste banks to support environmental management and local economic development in the Mount Lawu area, and (7) develop a community-based waste bank development model to support environmental management and local economic development in the Mountain area Lawu. This research is a descriptive study with a qualitative approach. The research data was collected using several methods, namely field observations, interviews, focus group discussions (FGD / Focus Group Discussion), and document review methods. Data were analyzed using interactive analysis and internal and external environmental analysis (ALIE). The outputs of this study are: (1) the model and strategy for developing waste banks to support environmental management and local economic development in the GunungLawu area, and (2) publication of scientific articles in nationally accredited journals.